Italian pediatric respiratory society recommendations on pediatric pulmonary function testing during COVID-19 pandemic - Elisabetta Bignamini; Salvatore Cazzato; Renato Cutrera; Giuliana Ferrante; Stefania La Grutta; Amelia Licari; Enrico Lombardi; Fabio Midulla; Giorgio Piacentini; Massimo Pifferi; Francesca Santamaria; Giancarlo Tancredi; et al. (BMC, 2020)
Abstract Background Effective prevention and control strategies are mandatory to prevent SARS-CoV-2 infection. Main text The Italian Pediatric Respiratory Society promotes a series of new recommendations that should be followed in pulmonary function testing laboratories during the COVID-19 pandemic. Conclusion Pulmonary function testing should be performed in children with chronic lung disease only if it is needed to guide management and limited to the necessary tests, namely spirometry. When performed, strict infection control measures should be followed due to the potential risk of transmitting SARS-CoV-2.